2016
DOI: 10.1097/adm.0000000000000206
|View full text |Cite
|
Sign up to set email alerts
|

Abuse Potential of Oral Phendimetrazine in Cocaine-dependent Individuals

Abstract: Objectives Phendimetrazine is a prodrug for the monoamine releaser phenmetrazine, a drug with known abuse potential. Preclinical studies suggest that phendimetrazine has limited abuse potential and may have promise as an agonist-like replacement therapy for cocaine dependence. This study evaluated the abuse potential of phendimetrazine in humans. Methods Nine cocaine-dependent individuals (N = 9) were enrolled to investigate the abuse potential of phendimetrazine and d-amphetamine using a double blind, place… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Human self-administration studies (Greenwald et al, 2010; Rush et al, 2010) and clinical trials (Mooney et al, 2009) show that amphetamine treatment decreases cocaine intake. Similar to amphetamine, phenmetrazine acts as a monoamine reverse transport releaser, however in contrast to amphetamine, phenmetrazine when given orally in the form of its prodrug phendimetrazine has relatively low abuse liability (Bolin et al, 2016). Moreover, heart rate measures in human cocaine users have shown that phendimetrazine is safe and tolerable across a threefold span of doses alone and when combined with cocaine (Bolin et al, 2016; Stoops et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Human self-administration studies (Greenwald et al, 2010; Rush et al, 2010) and clinical trials (Mooney et al, 2009) show that amphetamine treatment decreases cocaine intake. Similar to amphetamine, phenmetrazine acts as a monoamine reverse transport releaser, however in contrast to amphetamine, phenmetrazine when given orally in the form of its prodrug phendimetrazine has relatively low abuse liability (Bolin et al, 2016). Moreover, heart rate measures in human cocaine users have shown that phendimetrazine is safe and tolerable across a threefold span of doses alone and when combined with cocaine (Bolin et al, 2016; Stoops et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…We chose to study the mGluR2/3 agonist, LY379268, given the fact that mGluR2/3 receptors are altered following cocaine self-administration. We also chose to study the monoamine releaser, phenmetrazine, given its ability to increase dopamine tone in a manner similar to amphetamine combined with the fact that in the clinic it can be administered orally via its prodrug, phendimetrazine, which exhibits relatively low abuse potential compared to other proposed agonist therapies like amphetamine (Bolin et al, 2016). Finally, we chose to investigate the combined effects of these compounds given increasing interest in the ability of combination therapy to reduce self-administration to a greater extent than monotherapy in addition to the fact that these drugs have been proposed to reduce cocaine self-administration, in part, through distinct mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…No medications are currently approved to treat cocaine use disorder, and most candidate pharmacotherapies have demonstrated limited impact on drug‐taking behavior (see reviews by Czoty, Stoops, & Rush, ; Kampman, ; Karila et al, ). Those with demonstrated efficacy have a perceived increased potential for abuse and diversion, limiting their adoption (Bolin, Stoops, Sites, & Rush, ). Identifying novel effective pharmacological treatments that would be more readily adopted is a clear research priority given the negative economic and public health consequences of continued cocaine use.…”
Section: Introductionmentioning
confidence: 99%
“…JPET/2020/264952.R1 13 cocaine ("stimulant" and "talkative/friendly"), it does not attenuate most of the positive subjective effects (e.g., "euphoric," "high" or "like drug") or the reinforcing effects of cocaine (Bolin et al 2016;Stoops et al 2019). The clinical implication of these results is that despite the ability to reduce cocaine self-administration in laboratory animals, the potential for abuse may limit the clinical potential of PDM; our goal was to determine whether that abuse potential was lower than cocaine.…”
Section: Downloaded Frommentioning
confidence: 99%